THE ROLE OF THE TRANSFORMATIONAL TEACHER PROGRAM IN FOSTERING TEACHER COLLABORATION - Jamaludin, Ujang; Suharjuddin, Suharjuddin; Awiria, Awiria (Universitas Labuhanbatu, 2025)
Purpose–This research aims to analyze the impact of the Transformational Teacher Program on enhancing teacher collaboration competence in elementary schools in Bekasi City. Teacher collaboration is a critical skill in addressing the demands of 21st-century education. The program is designed to develop teachers as learning leaders who can collaborate and innovate within professional learning communities.Methodology–This study employs a qualitative descriptive approach using a case study design. Ten elementary schools in Bekasi were selected purposively as research sites. Data were collected through in-depth interviews with teachers and principals, direct observation of collaborative practices, and analysis of program-related documents. The data were then systematically analyzed to uncover field findings.Findings–The findings reveal that the Transformational Teacher Program has had a significant positive impact on promoting collaborative practices. Teachers reported increased sharing of best practices, development of innovative teaching strategies, and greater engagement in inter-school professional networks. However, some challenges remain, including high administrative workload and limited time for participation.Contribution–Despite obstacles in its implementation, the program has improved teaching quality and strengthened relationships between teachers and schools. Research findings support broader education reform and inform policy formulation, particularly improving teacher competency through community-based professional development. This study benefits policymakers, school leaders, and educators seeking to enhance professionalism and collaboration in elementary education.